Survival outcomes of patients with extranodal natural-killer T-cell lymphoma: a prospective cohort study from the international T-cell Project. Issue 4 (April 2020) - Fox, Christopher P; Civallero, Monica; Ko, Young-Hyeh; Manni, Martina; Skrypets, Tetiana; Pileri, Stefano; Kim, Seok Jin; Cabrera, Maria Elena; Shustov, Andrei R; Chiattone, Carlos S; Horwitz, Steven M; Dlouhy, Ivan; et al.
Summary: Background: Extranodal natural killer (NK) T-cell lymphoma (ENKTL) is a unique clinicopathological entity, typically associated with poor survival outcomes. Most published data have come from east Asian study groups, with little information available from international cohorts. The effects of treatment advances on routine clinical practice across continental territories has not been clear. We aimed to improve understanding of the clinical characteristics and outcomes of patients with ENKTL. Methods: We did a substudy of patients with ENKTL from the T-cell Project, a global prospective cohort study. The T-cell Project registered consecutively diagnosed adults (>18 years) with newly diagnosed, untreated mature T-cell or NK lymphomas (WHO 2001 or 2008 classifications) from 74 centres in 13 countries (in Asia, Europe, North America, and South America). In total, 1695 patients with mature T-cell or NK lymphomas were enrolled between Oct 12, 2006 and Feb 28, 2018 in the T-cell Project. The first patient with ENKTL was enrolled on Feb 15, 2007, and the last on May 26, 2017. Data on baseline characteristics, first-line treatment, treatment response, and survival outcomes were recorded in a central database (locked March 30, 2019). The primary outcome was 5-year overall survival. The T-cell Project is registered on ClinicalTrials.gov, NCT01142674 . Findings: 166 patients were diagnosed with ENKTL, comprising 11% of 1553 eligible registered cases and distributed across 40 participating centres in four continents. At a median follow-up of 44 months (IQR 20–61), overall survival at 5 years was 54% (95% CI 44–63) in patients with nasal disease (n=98) and 34% (27–46) in patients with extranasal disease (n=68). Interpretation: To our knowledge, this study presents the largest international cohort of patients with ENKTL. We describe a clinically significant improvement in the survival of patients with ENKTL treated in routine clinical practice over the past decade, likely to be attributable to the increasing use of treatment protocols specific for ENKTL. Funding: The Fondazione Cassa di Risparmio di Modena, the Associazione Angela Serra per la Ricerca sul Cancro, the Fondazione Italiana Linfomi, Allos Therapeutics, Spectrum Pharmaceuticals, Associazione Italiana per la Ricerca sul Cancro, and the National Cancer Institute at the National Institutes of Health.